Oryza sativa cv. Inpago 10 Shows Significant Drought Tolerance Differences Based on Relative Water Content (RWC) for National Food Sovereignty - Ramadhan, Daffa Putra; Fendiyanto, Miftahul Huda; Sihombing, Okta Dwi Ellisia; Vardhana, Dustyn Putra (MUNISI: Military Mathematics and Natural Sciences, 2025)
Rice (Oryza sativa) is a key staple crop in Indonesia. This study focuses on using Relative Water Content (RWC) in Oryza sativa cv. Inpago 10 to deepen the understanding of drought tolerance and contribute data that supports national food sovereignty. The RWC measurement involves weighing fresh leaf samples, soaking them in distilled water for 24 hours, re-weighing them to obtain turgid weight, drying them at 60°C for 24 hours, and then measuring their dry weight. The RWC is calculated using a specific formula. The experimental design follows a Randomized Complete Block Design, with Inpago 10 subjected to drought stress and Inpago 5 serving as the control. Results show that Inpago 10 retains water more effectively during drought stress compared to Inpago 5. This research advances understanding of drought tolerance and could facilitate the development of more resilient rice varieties, thereby strengthening national food sovereignty.